Intranasal lidocaine administration via mucosal atomization device: a simple and successful treatment for postdural puncture headache in obstetric patients - Siegler, Benedikt Hermann; Dos Santos Pereira, Rui Pedro; Keßler, Jens; Wallwiener, Stephanie; Wallwiener, Markus; Larmann, Jan; Picardi, Susanne; Carr, Richard; Weigand, Markus A.; Oehler, Beatrice (Biomedicines, 2023)
(1) Background: Postdural puncture headache (PDPH) remains a serious complication in obstetric patients. While the epidural blood patch represents the current gold standard in therapy, a growing number of alternative measures are thought to be beneficial for clinical management. The purpose of this study was to retrospectively analyze the efficacy of intranasal lidocaine administration to treat PDPH in obstetrics at our university hospital; (2) Methods: A retrospective analysis of the medical records of patients with PDPH has been performed focusing on the techniques of administration, dosing, treatment duration, impact on pain intensity as well as side effects of intranasal lidocaine; (3) Results: During the study period, 5610 obstetric patients received neuraxial anesthesia, of whom 43 (0.77%) developed PDPH. About one third of the patients with PDPH after spinal anesthesia (n = 8), epidural anesthesia (n = 5) or both (n = 2) were treated with intranasal lidocaine. Lidocaine was administered either via gauze compresses (GC, n = 4), a mucosal atomization device (MAD, n = 8) or with a second-line mucosal atomization device due to low gauze compress efficacy (n = 3). All patients treated with lidocaine refused the epidural blood patch. Nebulization of lidocaine resulted in a significant reduction in pain intensity after the first dose (p = 0.008). No relevant side effects developed except sporadic temporal pharyngeal numbness. The utilization of the mucosal atomization device averted the necessity for an epidural blood patch, whether employed as the primary or secondary approach; (4) Conclusions: Our data imply that the mucosal atomization device enhances the efficacy of intranasal lidocaine administration in obstetric patients suffering from PDPH.
Gesehen am 23.02.2024